2021
DOI: 10.3389/fphar.2021.652335
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Approach in the Identification of Potential Therapeutic Biomolecule for COVID-19

Abstract: COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It has a disastrous effect on mankind due to the contagious and rapid nature of its spread. Although vaccines for SARS-CoV-2 have been successfully developed, the proven, effective, and specific therapeutic molecules are yet to be identified for the treatment. The repurposing of existing drugs and recognition of new medicines are continuously in progress. Efforts are being made to single out plant-based novel therapeutic compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 205 publications
(192 reference statements)
0
9
0
Order By: Relevance
“…One promising method for identifying the factors causing complex diseases is an integrative approach that combines omics technologies, such as microbiomics, transcriptomics, and metabolomics (Hasin et al ., 2017 ). Although this approach has been widely used in studies of human diseases, including cancer (Menyhárt and Győrffy, 2021 ), cardiovascular disease (Leon‐Mimila et al ., 2019 ), and COVID‐19 (Singh et al ., 2021 ), it has rarely been used to study plant diseases. Here, we utilized a multi‐omics approach to identify the bacterial, fungal, and viral communities associated with SGS at the main soybean production site in China, using amplicon (16S and ITS), RNA, and small RNA sequencing approaches.…”
Section: Introductionmentioning
confidence: 99%
“…One promising method for identifying the factors causing complex diseases is an integrative approach that combines omics technologies, such as microbiomics, transcriptomics, and metabolomics (Hasin et al ., 2017 ). Although this approach has been widely used in studies of human diseases, including cancer (Menyhárt and Győrffy, 2021 ), cardiovascular disease (Leon‐Mimila et al ., 2019 ), and COVID‐19 (Singh et al ., 2021 ), it has rarely been used to study plant diseases. Here, we utilized a multi‐omics approach to identify the bacterial, fungal, and viral communities associated with SGS at the main soybean production site in China, using amplicon (16S and ITS), RNA, and small RNA sequencing approaches.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Singh et al . argued that the multi-omics approaches offered various tools and strategies for identifying potential therapeutic biomolecules for COVID-19, and they explored the available multi-omics approaches [ 156 ]. In addition, Stephenson et al .…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Müller et al showed that silvestrol inhibits the replication of HCoV-229E and MERS-CoV by suspending cap-dependent viral mRNA translation [ 41 ]. Various studies have shown that silvestrol can inhibit the eIF4A-dependent translation of viral mRNA of EBOV, ZIKV and hepatitis E virus [ 42 , 43 ]. A study by Henss et al also showed that silvestrol can delay protein synthesis of the chikungunya virus and reduce viral RNA replication [ 44 ].…”
Section: Discussionmentioning
confidence: 99%